Big apple battleground ebook - Wein, Len (Amazing Spider-Man Epic Collection., 2024)
Collects Amazing Spider-Man (1963) #165-185, Amazing Spider-Man Annual (1964) #11-12, Nova (1977) #12 And Marvel Calendar 1978. J. Jonah Jameson has uncovered proof that Peter Parker is Spider-Man - and that's just the beginning of the web-slinger's problems! Dinosaurs are fighting the Lizard on Broadway. Doctor Faustus plots to drive our hero insane. And the Molten Man and Punisher are back in town! That's just another day in the Big Apple for Spider-Man! But when the Green Goblin returns, all bets are off! Spider-Man's secret identity, the lives of Aunt May and Mary Jane - everything is on the line! Also featuring a team-up with Nova, the first appearance of Rocket Racer, the return of the crime boss Silvermane, an Annual with more spiders than men…and Peter Parker proposes to Mary Jane! Will she accept?